The Effect of Phrase-Cued Text Strategy on Studentsâ Reading Comprehension - Ridianto, Ridianto; Desfiyenti, Desfiyenti; Hasibuan, Dumariana (AT-TALIM, 2018)
Reading is an activity to get information from the written text. However, the students still have didifficulty when they read. So, to solve the studentsdstudents problems, the researchers used Phrase - Cued text (PCT) strategy in teaching reading. The purpose of this research was to know the significant effect of teaching reading by using PCT at the eight grade students of SMPN 2 Harau in 2016/217 academic year. This research was an experimental research. The population of this research was the eight grade students of SMP N 2 Harau in 2016/2017 academic year. There were seven classes of eight grade. The sample of this research chosen by using cluster sampling. The experimental class was VIII.6 had been taught by using PCT and the control class was VIII. 7 had been taught by using conventional strategy. The instrument of this research was reading test in multiple choice form. It was valid because the students have learnt the material and had been stated in syllabus and based on curriculum. Then, the instrument was reliable because the coefficient of reliability of split half was 0.78. The researchers analyzed the data by using t-test suggested by Gay et Al. The result of the data analysis was t-calculated (3.97) > t-table (2.042) where the level of significant was 0.05 with degree freedom was 38. H0 was rejected and H1 was accepted. So, it can be concluded that there was significant effect of teaching reading by using PCT strategy at the eight grade students of SMP N 2 Harau.So, it is suggested for English teacher to use this PCT strategy in reading lesson.